Central retinal artery catheterization for retinal artery occlusion with balanced salt solution - Xiangdong Luo; Xiaoying Wang; Yang Li; Xiaoyan Chen; Bin Wang; Qinrui Hu; Xiaoxin Li (Scientific Reports)
Abstract To assess the efficacy and safety of vitrectomy combined with central retinal artery Cannulation in the treatment of retinal artery occlusion. Retrospective case analysis was conducted from April 2020 to March 2022 at the Xiamen Eye Center of Xiamen University, for patients diagnosed with central retinal artery occlusion or branch retinal artery obstruction, who underwent retinal artery Cannulation within 72 h of onset. All patients underwent pre- and postoperative visual acuity, intraocular pressure, fundus photography, optical coherence tomography, wide-angle fluorescein angiography, and visual field examination. Nine patients (6 males and 3 females) with an average age of 46 ± 28.6 years (range: 16–77 years) were included. Seven eyes were diagnosed with central retinal artery occlusion, and two eyes with branch retinal artery occlusion. The average time from onset to surgery was 40.1 h. One month after treatment, logMAR visual acuity improved in all 9 eyes of 9 patients, with a statistically significant difference (P = 0.012). Fluorescein angiography showed that postoperative arm-retinal circulation time was shortened in 5 cases (5/9, 55%) and unchanged in 4 cases (4/9, 45%). After surgery, patients generally report an improvement in vision, as well as an enhancement in their field of vision. Retinal artery Cannulation can effectively improve visual acuity and visual field, shorten the arm-retinal circulation time, and promote the recovery of retinal circulation.